The Efectiveness Of Cognitive Behavioral Therapy (CBT) In Reducing Anxiety In Pregnant Women - Illustri, Illustri (Sean Institute, 2024)
Anxiety in pregnant women can arise due to the long process of waiting for birth. Every pregnant woman is vulnerable to stress that continues to the stage of depression. Stress and depression disorders based on the facts that are developing today show an increase from year to year. Where pregnant women are vulnerable to stress and depression disorders because they experience physical and psychological changes, as well as role changes from pregnancy, labor, postpartum and worries about taking care of the baby, besides that women are 3.01 times at risk of experiencing anxiety compared to men. Recent studies have shown that pregnant women experience as much as 37 percent anxiety. In addition, reviews of cognitive behavioral therapy for perinatal mental health have largely focused on depression, with far less attention given to anxiety and stress. Therefore, researchers are interested in conducting research on the effectiveness of cognitive behavioral therapy in reducing anxiety in pregnant women in the working area of Makrayu Community Health Center. The design of this study was a quasi-experiment, the sample was pregnant women who visited the obstetrics clinic at the makrayu health center. The number of samples was 15 people in the experimental group and 15 people in the control group with purposive sampling technique. To measure anxiety levels using the TMAS instrument (Taylor Manifest Anxiety Scale). The data that has been obtained is processed and analyzed by t test using SPSS program. From the results of the study it can be concluded that the results of the t-test obtained a significance value of 0.000, this means